Ethical Perceptions of Tax Evasion for Small Business Taxpayers - Ifada, Ardhelia; Ginting, Yoremia Lestari (AFEBI Economic and Finance Review, 2023)
This study aims to examine the effect of tax justice, the tax system, tax discrimination, and the love of money on tax evasion. This type of research was carried out by quantitative research and using primary data. The population in this study is MSME taxpayers who are registered at the Samarinda Ilir and Ulu Tax Office. The sampling method used purposive sampling, the data obtained by 75 small business taxpayer respondents through distributing questionnaires and Google forms. The analytical method for managing data uses multiple regression analysis in the SPSS 29 application, and in analyzing the data in this study using descriptive statistics, classical assumption tests, and hypothesis testing. The theory used in this study is the Theory of Planned Behavior (TPB) using three components, namely attitudes toward behavior, subjective norms, and behavioral control. The results of this study indicate that the four variables have a positive and significant effect on tax evasion